(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
Because elementary school students lack a thorough synthesis between comprehension, pronunciation, and comprehension of text, they make mistakes in their mother tongue and reading literacy. This makes it difficult to understand the content of the text.